1985
DOI: 10.1037/0033-295x.92.4.548
|View full text |Cite
|
Sign up to set email alerts
|

An attributional theory of achievement motivation and emotion.

Abstract: A theory of motivation and emotion is proposed in which causal ascriptions play a key role. It is first documented that in achievement-related contexts there are a few dominant causal perceptions. The perceived causes of success and failure share three common properties: locus, stability, and controllability, with intentionality and globality as other possible causal structures. The perceived stability of causes influences changes in expectancy of success; all three dimensions of causality affect a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

219
5,578
28
505

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,956 publications
(6,330 citation statements)
references
References 124 publications
219
5,578
28
505
Order By: Relevance
“…Exceptions to this are studies finding no relation between searching for meaning and adjustment (Gotay, 1985;Taylor et al, 1984). Theoretically (Michela and Wood, 1986;Silver et al, 1983;Weiner, 1985), searching for meaning could be associated with better adjustment if, for example, it enabled individuals to find meaning, or to identify benefits or positive outcomes associated with their cancer, such as closer relationships with others, a spiritual reawakening, or a greater appreciation of life. However, to our knowledge, there are no studies that have shown a positive association between searching for meaning and adjustment.…”
Section: Introductionmentioning
confidence: 97%
“…Exceptions to this are studies finding no relation between searching for meaning and adjustment (Gotay, 1985;Taylor et al, 1984). Theoretically (Michela and Wood, 1986;Silver et al, 1983;Weiner, 1985), searching for meaning could be associated with better adjustment if, for example, it enabled individuals to find meaning, or to identify benefits or positive outcomes associated with their cancer, such as closer relationships with others, a spiritual reawakening, or a greater appreciation of life. However, to our knowledge, there are no studies that have shown a positive association between searching for meaning and adjustment.…”
Section: Introductionmentioning
confidence: 97%
“…"Causal attribution" refers to the thoughts that a child has, which identifies the actor responsible for an observed social stimulus (Weiner, 1985). In addition to causal attributions, attributions of intent occur within this step when a child takes the perspective of another person involved in the social event (Crick & Dodge, 1994).…”
Section: Attribution Formationmentioning
confidence: 99%
“…In the specific realm of attribution formation, Weiner (1985) asserted that causal attributions predict how one later feels about a social stimulus as well as how one responds to it.…”
Section: Attributions and Behaviormentioning
confidence: 99%
“…Causal attributions are the common-sense explanations people give to account for an event and their own interpretations which will guide future behaviours [7][8][9][10]. Various studies [11][12][13] have highlighted how much causal attributions influence cognitions and symptom experience but also contribute to determine the illness response, help-seeking behaviour, illness-associated disability as well as coping behaviour and adaptive resources in various illnesses, including heart infarction [14], somatoform disorders [15,16], somatoform disorders in patients with suspected allergies [17], orthopaedic surgery [18], chronic pain [19], fatigue [20,21] and fibromyalgia [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed the importance of two additional dimensions which may influence affective and behavioural responses to stressful events: stability over time and controllability of the event [9,10,[24][25][26]. Causal attributions can be thus classified into three dimensions: 1) locus of causality, 2) stability, and 3) controllability [26].…”
Section: Introductionmentioning
confidence: 99%